Clinical evaluation of abutment teeth of removable partial denture by means of the Periotest method - Jorge, Janaina Habib [UNESP]; Giampaolo, E. T.; Vergani, Carlos Eduardo [UNESP]; Machado, Ana Lucia [UNESP]; Pavarina, Ana Claudia [UNESP]; Cardoso de Oliveira, M. R. (Blackwell Publishing, 2007)
Prosthodontics should be one of the means of establishing conditions for the maintenance of periodontal health. The forces applied to the abutment teeth and their effects are very important considerations in the design and construction of the removable partial dentures. This 6-month follow-up clinical study evaluated the degree of mobility of abutment teeth of distal extension and tooth supported removable partial dentures by using Periotest. Two types of clasp design were selected for evaluation. In cases with unilateral and bilateral distal-extension, a clasp design including a T clasp of Roach retentive arm, a rigid reciprocal arm and a mesial rest were used. For the abutments of tooth-supported removable partial dentures, a second clasp design with a cast circumferential buccal retentive arm, a rigid reciprocal clasp arm and a rest adjacent to the edentulous ridges was selected. A total of 68 abutment teeth was analysed. Periotest values were made at the time of denture placement (control) and at 1, 3 and 6 months after the denture placement. The statistical analysis was performed using Friedman test. All analysis was performed at a 0.05 level of significance. The results revelled that no significant changes in tooth mobility were observed during the 6-months follow-up (P > 0.05). In conclusion, our findings suggest that adequate oral hygiene instructions, careful prosthetic treatment planning and regular recall appointments play an important role in preventing changes in abutment tooth mobility caused by removable partial denture placement.
Keywords: mobility; removable partial denture; abutment teeth; prosthodontics; design